The effect of conscientiousness, openness to experience, and neuroticism on military identity in a South African military university: the moderating role of Selflessness - Solomons, Timothy Lydhann Dugald (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMil)--Stellenbosch University, 2023.